Isolated truncus arteriosus associated with a mutation in the plexin‐D1 gene. Issue 12 (29th October 2013) - Ta‐Shma, Asaf; Pierri, Ciro Leonardo; Stepensky, Polina; Shaag, Avraham; Zenvirt, Shamir; Elpeleg, Orly; Rein, Azaria J.J.T.
Abstract: Truncus arteriosus accounts for approximately 1% of congenital heart defects and the cause of isolated non‐syndromic truncus arteriosus is largely unknown. In order to identify the underlying molecular defect in a consanguineous family with recurrent tuncus arteriosus, homozygosity mapping followed by whole exome sequencing was performed. This resulted in the identification of a homozygous mutation, Arg1299Cys, in the PLXND1 gene. The mutation affected a highly conserved residue, segregated with the disease in the family and was absent from available SNP databases and ethnic matched controls. in silico comparative modeling revealed that the mutation resides in the N‐terminal segment of the human plexin‐D1 intracellular region which interacts with the catalytic GTPase‐activating protein homology region. The mutation likely destabilizes the intracellular region, perturbing its anchoring and catalytic activity. The phenotype in human PLXND1 mutation is closely related to that of knockout mice for PLXND1, its co‐receptor neuropilin‐1 or its ligand SEMA3C . It is therefore suggested that SEMA3C signaling, propagated through the heterodimer receptor plexin‐D1/neuropilin, is important for truncus arteriosus septation. Confirmation of this observation will require the identification of PLXND1 mutations in additional patients. Exome analysis is valuable for molecular investigation of single patients with congenital heart defects in whom chromosomal copy number variants have been excluded. © 2013 Wiley Periodicals, Inc.